Comparative histomorphological study of non affected and affected bile duct and gall bladder by fascioliasis in Black Bengal Goat (Asian Journal of Medical and Biological Research, 2018)
The purpose of this study was to comparative histomorphological investigation of the non affected and affected bile duct and gall bladder by fascioliasis in Black Bengal goat. The average weight of affected gall bladder was 26.10±0.70 gm which was significantly (p